An Investigation of the Socio-Economic Implications of the Violation of Land Use Laws in Kpakungu Area of Minna, Niger State, Nigeria - B.K., Maimuna; G.N., Nsofor; Y.M., Suleiman (Asian Review of Environmental and Earth Sciences, 2014)
Over the years, there has been a rapid increase in population of people and socio-economic activities at kpakungu. The major reasons for this increase have been ascribed to the number of investments and socio-economic activities which have culminated in increased and deplorable living conditions. The residents, who are in desperate need of shelter to provide accommodation, tend to develop properties without taking account of the land use planning pattern or zoning regulation, thereby building properties that are not in conformity with the planning regulations. This study is aimed at investigation of the Socio-economic Implications of the Violation of Land Use Laws in Kpakungu Area of Minna and the state and rate of compliance with these laws. Questionnaire administration, Personal interview and field analysis were utilised. The results indicate that the population growth and socio-economic activities in Kpakungu have led to over stretching of facilities which encouraged over-crowding in the area and attendant consequences such as the growth of slums due to lack of plan and alteration to Minna city Master Plan. Therefore, State Government should review the laws enacted ensuring that households abide by such laws and set a fine for non-compliance with the laws. There is also the need to establish a housing policy to provide sufficient and affordable housing for the lower income group so that illegal sub-divisions on buildings for residential purposes can be eliminated.